Levels of awareness, current treatment trend and knowledge of Malaysian Physiotherapists in treating patients with Temporomandibular Joint Disorder (TMD)/ Nur Ardilla Mohd Azlan Goh, Norazlin Mohamad, Saiful Adli Bukry - Mohd Azlan Goh, Nur Ardilla; Mohamad, Norazlin; Bukry, Saiful Adli (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Temporomandibular disorders (TMD) is a musculoskeletal disorder involving the muscles of masticatory, temporomandibular joint (TMJ) and other associated structures that affect at least a quarter of the general population and the management of TMD are available surgically and non-surgically. In contrast, the most recommended approach would be non-surgical, which is physiotherapy. The main goal of physiotherapy is to regain normal mandibular function. Managing TMD is known to be challenging to practitioners, and knowledge frequently has influenced it. This study aims to investigate the levels of awareness, current treatment trends, and knowledge of Malaysian physiotherapists in treating patients with the temporomandibular joint disorder (TMD). A total of 94 physiotherapists in Malaysia participated in this study. A questionnaire consists of four parts related to awareness, knowledge, and treatment approach of TMD distributed via Google form. Overall results showed a fair level awareness and fair level of knowledge among physiotherapists. The current treatment approach of TMD was found to be jaw exercise and manual therapy. There was no significant difference in the qualification of study and the number of years of working as a physiotherapist between the levels of knowledge, awareness, and treatment approach. Based on the findings, it is recommended that physiotherapists to update their knowledge and be more aware of the current treatment of TMD regardless of different qualification of study and the different number of years working in clinical settings.